2012
DOI: 10.1007/s10620-012-2387-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Markers for Early Diagnosis and Prognosis of Sporadic Pancreatic Ductal Adenocarcinoma

Abstract: Our study suggests that Adnab-9 may be an effective marker for diagnosis and prognosis of PDA. Adnab-9 may be reflective of the presence of Paneth cells confirmed by Defensin-5 staining. These cells may modulate the biological activity of the cancer and confer a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…26,27 Polymorphisms of HBD-1 and HBD-2 have been associated with severe acute pancreatitis, 28 and the detection of human defensin α 5 (HAD-5) in pancreatic metaplasia has been seen as an indicator of the adenoma-carcinoma sequence. 29 In the present study, HNP-1 was found to be expressed at a significantly higher level in malignant human pancreatic tissue than in healthy pancreas or in CP. These findings support the hypothesis that defensins, in particular HNP-1, may represent an important link between chronic inflammation and malignant transformation in the pancreas.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…26,27 Polymorphisms of HBD-1 and HBD-2 have been associated with severe acute pancreatitis, 28 and the detection of human defensin α 5 (HAD-5) in pancreatic metaplasia has been seen as an indicator of the adenoma-carcinoma sequence. 29 In the present study, HNP-1 was found to be expressed at a significantly higher level in malignant human pancreatic tissue than in healthy pancreas or in CP. These findings support the hypothesis that defensins, in particular HNP-1, may represent an important link between chronic inflammation and malignant transformation in the pancreas.…”
Section: Discussionsupporting
confidence: 49%
“…26,27 Likewise, severe acute pancreatitis has been associated with polymorphisms of defensin genes, 28 and defensins have been detected in pancreatic metaplasia. 29 We assume that disturbances of the regulative function of defensins, possibly triggered by chronic inflammation, could promote malignant transformation and tumor growth within the pancreas. During the inflammatory process, defensins may either be switched off or the cancer may abuse their functions.…”
mentioning
confidence: 99%
“…Adnab-9: Adnab-9 is a murine monoclonal antibody that has previously been implicated in the diagnosis of gastrointestinal tumors[ 448 , 449 ]. Adnab-9 detection in stools has a sensitivity and specificity of 80% and 87% for detection PC[ 450 , 451 ].…”
Section: Faecal Biomarkersmentioning
confidence: 99%
“…The presence of Adnab-9 in stools has been shown to be associated with PC precursor lesions. As a fecal biomarker, Adnab-9 has a sensitivity of 80% and a specificity of 87% for the detection of PC [ 25 ]. In the future, effective tumor markers can be used to aid in the diagnosis of the presymptomatic PC, treatment assessment, and then monitoring for disease recurrence.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%